BIOMECHANICAL APPROACHES TO LONG-TERM SPLINTING OF MOBILE TEETH IN PERIODONTITIS - Бєліков, Олександр; Бєлікова, Наталія; Сорохан, Микола (Modern engineering and innovative technologies, 2024)
The article presents a biomechanical approach to splinting that allows to maintain tooth mobility at the physiological level, evenly distribute and dampen the load, involve the periodontal muscle reflex in its regulation, which guarantees the preservation